Philippine army recruitment and selection process for civilian employee/ basis for standard employment policy - Pantalla, Daryl John P. (Parañaque City: Olivarez College, 2023)
This study aimed to assess the Philippine Army Recruitment and Selection Process for Civilian Employees. Likewise, it aimed to propose a policy as an output of the study, which he believes could significantly contribute to the welfare and development of the Philippine Army organization. The researcher utilized a quantitative descriptive research design as this method provides quantitative responses based on the information collected from the Civilian Human Resources from two (2) Groups of the Headquarters Philippine Army (HPA) and Headquarters and Headquarters Support Group (HHSG). In particular, their responses to the numeric survey questions were utilized to explore, identify, and critically analyze the implications of aspects related to the Recruitment of Civilian Human Resources under Republic Act 2260. A total of 195 Civilian Human Resources were respondents to the study. A sample size of 45 from HHSG, or 24%, and 150 from HPA offices, or 76%, is generated using Slovin's formula with a 0.05 margin of error or with a 95% level of significance. The result shows that most of the Civilian Human Resources have a favorable agreement towards the Philippine Army recruitment and selection process regarding publication, screening, background checking, and medical examination. Likewise, there is a solid positive agreement perception toward final hiring. Through this, proposals were provided to the Philippine Army on improving their recruitment and selection process, including the challenges encountered.
Master Thesis
Keywords: Recruitment; Selection; Civilian Employees; Philippine Army; RA 2260.